Pharmacokinetics, safety and tolerability of the novel β‐hCG derived immunomodulatory compound, EA‐230 - van Groenendael, Roger (Br J Clin Pharmacol, 2019)
AIMS: EA‐230 is a newly developed synthetic linear tetrapeptide (AQGV) derived from the chorionic gonadotropin hormone (β‐hCG). We investigated the pharmacokinetics, safety and tolerability of EA‐230 in healthy subjects using different administration strategies. METHODS: Double‐blind, randomized, placebo‐controlled, dose‐escalating phase I studies in healthy subjects using intravenous administration were conducted. In the single dosage study, 32 subjects were assigned to four single dosage groups (1, 3, 10 or 30 mg/kg). In the multiple dosage study, 24 subjects were assigned to three dosage groups (10, 20 or 30 mg/kg, thrice daily for 3 days). In the continuous dosage study, 24 subjects were assigned to three dosage groups (15, 30, or 90 mg/kg/hour for 2 hours). Pharmacokinetics, safety and tolerability assessments were performed up to 14 days. RESULTS: The highest dosage of EA‐230 (continuous infusion of 90 mg/kg/hour for 2 hours) showed more than proportional increases in exposure (C (max)136%; AUC(0‐last)137%), a large volume of distribution (geometric mean and 95% CI: 13 [3–58] L/kg), a high clearance rate (26 [15–43] L/h/kg), and a short half‐life (0.35 [0.13–1.0] minutes). EA‐230 was well tolerated and no safety concerns were observed. CONCLUSION: These dose‐escalating phase I studies with different administration strategies reveal a pharmacokinetic profile of EA‐230 with a large volume of distribution and a short half‐life. Furthermore, EA‐230 was well tolerated and no safety issues emerged. These results have enabled further clinical development in a phase IIa trial assessing the pharmacodynamics of this compound during systemic inflammation described elsewhere in this issue.